Sistem Kontrol Kecepatan Motor Exhaust Fan Pada Cooking Hood Menggunakan Metode Fuzzy - Devo Harwan Pradiansyah; Wijaya Kurniawan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In cooking activities, smoke has a risk to health. This is often underestimated by the community, especially women who are more often at kitchen. If the kitchen is a minimalist type where there is no air hole which causes air circulation in kitchen can not change and it is difficult to smoke to get out. Although it looks trivial, smoke actually has a bad impact on the health of the skin until breathing, it is caused by incomplete combustion smoke in the kitchen containing carbon monoxide (CO), SO2, and NO2 gas which if inhaled excessively can cause pneumonia and cancer. based on these problems there needs to be a system that is able to detect smoke and take action to remove it. In previous studies, there are studies on how to monitor levels of cigarette smoke in the room and regulate the flame on the fan. In this study, there are two kinds of inputs, namely MQ 2 sensor and MQ 7 sensor values ​​obtained from these sensors will be processed using fuzzy logic method whose results will be used as a consideration to run the output in the form of an accelerator on the fan according to the requirements needed based on the smoke conditions and CO gas contained in the air. This system also equipped with LCD which is useful for displaying the concentration of smoke and CO gas contained in the air and the required motor speed based on calculations on the fuzzy logic method. From the results of tests that have been carried out the system can run well in accordance with the design that has been done. Motor speed in this system change responsively according to changes of the concentration of smoke and CO gas.